Corrupting and Saving: Moral Contamination, Prison Education and Prison History. (11th October 2021) - JOHNSTON, HELEN
Abstract: This article examines the ways in which prison has been seen as both a 'school of crime' and a school of reform; a place for potential further corruption, or through education in prison, a route away from criminality. It explores the methods used, since the early 19th Century, to protect those confined from the corrupting prison environment. In examining prison education in the 1920s, it argues that, despite significant changes in the wider penal system, changes in education and schooling within prison walls, continued to be slow, protracted in developing, and ineffectual in the challenge of reforming prisoners.